(untitled) (Journal of the College of Basic Education, 2022)
Zinc is an active element in the body and behaves as a co-factor for many enzymes, so the aim of this study was to investigate the association between intestinal parasites and serum zinc level in children in Iraq, and the effect of parasitie infections on the nutrition, growth, and physiology of host is still poorly understood.